Geochemical data of rare earth-enriched sediments from the Western, Central North, and Eastern South Pacific - Jianlin Liao; Jieyun Chen; Xiaoming Sun; Yinan Deng; Yanjingyu Wang; Dajin Wang; Gang Hong; Lukas Klose; Andrea Koschinsky (PANGAEA, 2023)
Major and trace elements of four gravity sediments cores retrieved from the Western (159°46'E, 17°23'N), Central North (161°30'W, 13°14'N), and Eastern South Pacific (135°15'W, 14°46'S, and 129°6'W, 13°47'S) were analyzed in order to research the enrichment mechanism of rare earth elements in deep-sea sediments. Four representative layers of each core were treated by sequential extraction to separate mineral phases including Ca-phosphate, Mn oxides, Fe oxides, etc. The major and trace elements of the leaching solutions were measured to estimate the proportions of rare earth elements controlled by different mineral phases.